Um estudo enunciativo da poesia no livro didático: perspectivas para o ensino - Dornas, Nayara Fernanda (Universidade Federal de São Carlos, 2025)
This work seeks to answer the following questions: “What does poetry mean in textbooks from the semantics of enunciation?; How does poetry as a linguistic object function in textbooks?; And how to read and interpret it from an enunciative perspective?”. To this end, we use the theoretical notes developed by the linguist Luiz Francisco Dias (2018, 2021, 2022), who works with the notions of enunciative relevance, historical reference, perspective and enunciative networks, and also the concept of Epilinguistics presented by Wamser and Resende (2013). In view of this, our objectives are to analyze the word poetry and its developments in the textbook, as well as the poems and exercises that accompany them, and to propose a methodology for reading and interpreting poetry from the enunciative perspective of Dias (2018). For this, the following textbooks were selected: Se Liga na Língua for the 8th grade by Moderna publisher; Geração Alpha for the 7th grade by SM Educação, both belonging to PNLD 2020; and Ser Protagonista for high school by SM Educação, which belongs to PNLD 2021. We divided our reflection into three stages. In the first, we analyzed the word poetry and its developments based on enunciative networks to understand which meanings for poetry are mobilized in the didactic materiality. To do this, we observe the indexes of the textbooks, as well as the introductory statements of the chapters, and we understand, for example, that poem, Rap, Slam, Repente, cordel, converge to poetry, which means from various historical references and diverse enunciative pertinences. Then, still using the mechanism of enunciative networks, we analyzed the materiality of the poems and their exercises to understand how they work in the textbook and we found that poetry works as a kind of exemplification for the study of some subjects and for the concretization of these from activities that accompany it, that is, it works as a hive-example. In the third part, we propose a methodology in which we develop a step-by-step guide on how to read and interpret poetry through Enunciative Semantics developed by Dias (2018) and we also mobilized the works of Guimarães (2012, 2013) related to text analysis. Then, we performed analyses to demonstrate the effectiveness of this proposal. Finally, we understood that poetry and our method can greatly contribute to the teaching-learning process.
An enunciative study of poetry in the textbook: perspectives for teaching
Keywords: Poesia; Livro didático; Semântica enunciativa; Rede enunciativa; Poetry; Textbook; Enunciative semantics; Enunciative network; LINGUISTICA, LETRAS E ARTES